The Doctrine of Legitimate Expectations: Need for Limits - POIEDYNOK, Valeriia; KOLOHOIDA, Oleksandra; LUKACH, Iryna (Journal of Advanced Research in Law and Economics, 2018)
The article deals with the doctrine of legitimate expectations, which requires public authorities to respect reasonable expectations they have created with individuals, in particular, if such expectations have become the basis for investment. The jurisprudence of investment treaty tribunals and the European Court of Justice on the issue is examined. The approach of the latter is found to be preferable because of the clear limits imposed on the application of the doctrine. The options of the doctrine’s reception by Ukrainian law are considered.